The Capabilities of Strategic Innovation and It’s Impact on the Superiority of Organizations - Azeez, Entisar; Fadhil Ahmed, Shehenaz (Opción, 2019)
Banking activity is considered as the mainstay of the rest of the activities and other fields within the framework of the national economy. Banking organi- zations play a leading role in supporting the monetary and financial policy of the state. This requires an increase in its efficiency and superiority. The main problem Iraqi banks face is represented by their inability to cope with rapid developments and changes in the environment, which is negatively reflected on their distinction. Hence, this paper sheds light on the capabilities that could support their superiority and distinction. The current paper aims at showing the impact of capabilities of strategic innovation: on the superiority of organ- izations in the International Islamic Bank-one of the most important private banks operating in Iraq, Baghdad Branch. The problem of this paper has been determined in a number of inquiries, mainly: what is the effect of capabilities of strategic innovation: (dynamic strategic learning methods, organization- al features, and supply series traits) in the superiority of organizations? To achieve the paper’s aims and answer the problem’s inquiries, it is submitted to a sample of (55) employees who work in the Bank under the research field, out of (300) employees, distributed into (19) sections and units related to them. The questionnaire depends on a tool for measurement and collecting data and information. Using a set of tools, a group of spss v.25 statistical to analyze the relationship and impact has been achieved.By using a concluding program technology, a relationship of connection and impact among capabilities strategic innovation: on the total level and organizations superiority has been founded.